Rahasia Kedokteran dan Perlindungan Hukum Pasien Covid 19 - Esther Masri (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2022)
Medical confidentiality is a patient's right that must be protected in the administration of health services. Good relations between doctors or hospitals with patients occur because they are based on trust. There is a doctor's obligation to keep the patient's medical secret. During the Covid-19 pandemic, the disclosure of medical secrets became a controversial issue among the public. Doctors have an obligation to pay attention to the limitations in keeping secret and disclosing medical secrets to the public and must be based on the laws and regulations in Indonesia. This study uses normative juridical legal research, namely legal research conducted by researching library materials by analyzing various statutory provisions and data contained in the literature. The results of the study, show that medical secrets for Covid-19 patients can be opened on the basis of public interest, one of which is due to extraordinary events or outbreaks of infectious diseases. In fact, the disclosure of data on patients infected with Covid-19 is not an embarrassing situation so that Covid-19 patients will not be stigmatized and discriminated against from the public. This is done to reduce the spread of Covid-19.